2021
DOI: 10.1159/000513766
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Clinical Evaluation of Dual Inhibition with Pertuzumab and Trastuzumab Biosimilar SB3 in HER2-Positive Breast Cancer Patients

Abstract: <b><i>Background:</i></b> The addition of trastuzumab to standard chemotherapy has improved survival in patients with HER2-positive breast cancer in neoadjuvant, adjuvant, and metastatic settings. In higher tumor stages, the addition of pertuzumab is now a standard of care and associated with a favorable toxicity profile. We evaluated the safety and efficacy of the trastuzumab biosimilar SB3 in combination with pertuzumab in HER2-positive breast cancer patients. <b><i>Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
3
0
0
Order By: Relevance
“…Furthermore, concomitant medication was reported as related factor to loss of consciousness, the patient recovered without sequelae, and treatment was continued as planned. Comparable cardiac safety profiles of SB3 (as monotherapy or together with PTZ) and TRZ have been previously demonstrated in clinical trials and real-world settings [24, 31, 33‒36]. In this 4-year PMS study, two events of decreased LVEF but no CHF or cardiac dysfunction were reported, confirming the cardiac safety of SB3.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Furthermore, concomitant medication was reported as related factor to loss of consciousness, the patient recovered without sequelae, and treatment was continued as planned. Comparable cardiac safety profiles of SB3 (as monotherapy or together with PTZ) and TRZ have been previously demonstrated in clinical trials and real-world settings [24, 31, 33‒36]. In this 4-year PMS study, two events of decreased LVEF but no CHF or cardiac dysfunction were reported, confirming the cardiac safety of SB3.…”
Section: Discussionsupporting
confidence: 79%
“…† Data shown as n (%). *>5% in any group, p value for difference between SB3 ± CT versus SB3+PTZ ± CT. [24,31,[33][34][35][36]. In this 4-year PMS study, two events of decreased LVEF but no CHF or cardiac dysfunction were reported, confirming the cardiac safety of SB3.…”
Section: Discussionsupporting
confidence: 68%
“…Out of the 78 patients enrolled, 24 patients received neoadjuvant SB3 and 43 patients received neoadjuvant TRZ. tpCR rates were 50% in the SB3 group and 58% in the TRZ group, comparable with landmark neoadjuvant TRZ plus pertuzumab combination studies [ 28 , 29 , 30 ]. Bae et al reported real-world outcomes from a Korean-based population with early-stage or metastatic HER2+ breast cancer.…”
Section: Introductionsupporting
confidence: 81%